Perception and acceptable risks – the union of decision-theory, behaviour and the brain. (7th May 2010) - Ricci, Paolo F.
Acceptability and perception drive risky environmental heath and safety decisions: protecting against nearly infinitesimal risks can involve expenditures of millions or billions of dollars. Societal decision-makers and individual taxpayers are asked to understand numbers that span over more than 15 orders of magnitude, numbers with which most individuals lack experience. For example, we perceived real estate values will continue to rise, and lenders, in part misperceiving the potential risks of defaults, lent to more than 7 million high-risk borrowers: more than a trillion dollars were involved in the sub-prime loans market disaster. Even when public agencies or industry perform a health or safety assessment and demonstrate low risk, such assertions are not sufficient justification for those at risk to accept as minimal guarantees of safety, as the Challenger disaster shows. However, to assert that a risk is correctly perceived and acceptable requires understanding of 'acceptable risk' numbers, otherwise any 'acceptable risk criterion' to justify a choice can hardly be meaningful. This paper's synthesis of theoretical and experimental aspects integrates decision-theoretic, behavioural and neurological results, including surprising or paradoxical choices.